QUALITY OF FRUITS IN TOMATO (Lycopersicon esculentum Mill.) LANDRACES FROM MEXICO - MENDEZ Infante, Isaura; VERA Guzmán, Aracelli Minerva; CHAVEZ Servia, Jose Luis; CARRILLO Rodríguez, Jose Cruz (Vitae, 2011)
Mexico is a center of domestication and diversification of tomatoes, with various landrace cultivated populations and wild varieties, but they are poorly documented in terms of their physical, chemical and nutritional characteristics. In order to evaluate the lycopene content, ascorbic acid and other physicochemical characteristics of a sampling of tomato fruits originating from different regions of Mexico, as well as evaluate the effect of storage on lycopene loss, a collection of thirteen accessions was made and later it was sown in greenhouse conditions under a randomized complete block design with four replications. The analysis of variance show significant differences (P < 0.05) among accessions for titratable acidity, pH, lycopene on wet and dry basis, in the CIE chromaticity coordinates L *, a * b *, and in the maturity index. Accessions GTO-11, OAX-115, PH-102 and PH-96 stood out for their lycopene content on a wet and dry basis with values above 20 and 300 mg 100 g-1, respectively. Lycopene content in samples of ground tomato fruits decrease with storage time at -20ºC, even in the scalded samples immersed in boiling water.